2008
DOI: 10.1111/j.1540-8175.2007.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Dysfunction and Asymmetrical Deformation of Mitral Annular Geometry in Ischemic Mitral Regurgitation: A Novel Computerized 3D Echocardiographic Analysis

Abstract: This novel 3D echo method demonstrated that MA motion and dilatation were asymmetric in IMR and symmetric in DMR. These differences in MA geometry and motion may aid in the development of distinct new therapies for IMR and DMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 30 publications
2
35
0
1
Order By: Relevance
“…The availability of this software sparked new research aimed at improved characterization of the mechanisms leading to mitral regurgitation. [75][76][77][78] Recent studies characterizing the mitral valve apparatus in nonischemic and ischemic cardiomyopathy have demonstrated geometric differences in mitral annular deformation with increased intercommissural and anteroposterior dimensions compared with healthy individuals, coupled with increased leaflet tenting and cordal tethering. 79 -81 Similarly, in patients with MI, the mitral annulus was found to be more dilated and flattened and further deformed in anterior versus posterior infarction.…”
Section: Mor-avi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of this software sparked new research aimed at improved characterization of the mechanisms leading to mitral regurgitation. [75][76][77][78] Recent studies characterizing the mitral valve apparatus in nonischemic and ischemic cardiomyopathy have demonstrated geometric differences in mitral annular deformation with increased intercommissural and anteroposterior dimensions compared with healthy individuals, coupled with increased leaflet tenting and cordal tethering. 79 -81 Similarly, in patients with MI, the mitral annulus was found to be more dilated and flattened and further deformed in anterior versus posterior infarction.…”
Section: Mor-avi Et Almentioning
confidence: 99%
“…In contrast, in patients with ischemic mitral regurgitation, LV remodeling caused by abnormal inferior wall motion results in uneven papillary muscle displacement and asymmetrical localized tethering associated with eccentric mitral regurgitation. 78,84 In addition, the characteristics of the mitral annular function were compared between patients with hypertrophic cardiomyopathy and LV hypertrophy secondary to hypertension or aortic stenosis. 87 Annular function in the LV hypertrophy group was similar to that of normal control subjects, whereas annular apical-basal motion and annular area changes were reduced in hypertrophic cardiomyopathy.…”
Section: Mor-avi Et Almentioning
confidence: 99%
“…Using three-dimensional (3D) echocardiography, Daimon et al [23] showed that annular dilation results in annular asymmetry during systole [24]. Furthermore, changes in annular motion are asymmetric, implying a role for regional LV dysfunction causing alterations in annular geometry that result in IMR.…”
Section: Pathophysiologymentioning
confidence: 98%
“…RT3D echocardiography has proven that in patients with functional mitral regurgitation due to dilated cardiomyopathy, symmetrical papillary muscle displacement leads to progressive cordal tethering and leafl et tenting, resulting in predominantly central mitral regurgitation as a result of decreased leafl et coaptation [38,39•,40]. On the other hand, in patients with ischemic mitral regurgitation, left ventricular remodeling caused by abnormal wall motion results in uneven papillary displacement and asymmetric tethering associated with eccentric mitral regurgitation [38,41,42]. It is well known that functional mitral regurgitation is a poor prognostic predictor in patients with left ventricular dysfunction [43][44][45].…”
Section: Assessment Of Mitral Valve Tenting In Functional Mitral Regumentioning
confidence: 98%